Law enforcement activities of the National Guard under martial law (Law and Safety, 2024)
The National Guard was established at the beginning of Ukraine’s independence, but began its development only after 2014. Its functioning is due to the threat to public security and order of the state, in particular from the Russian Federation. Instead, the National Guard of Ukraine is a military formation that performs law enforcement functions and demonstrates its potential under martial law. Due to the specifics of the structure of this formation, the concepts of “law enforcement function” and “law enforcement activity” are studied. Law enforcement activities during martial law consist in carrying out actions by specially authorized bodies aimed at protecting the rights, freedoms and interests of citizens, the interests of the State and comply with the form specified in law, taking into account the effect of martial law.It is noted that the National Guard of Ukraine has a number of features, such as adaptability, preventive activities and inextricable connection with the sphere of communications and communications. The law enforcement activities of the National Guard of Ukraine are multidirectional, which emphasises the unique role of this body as a hybrid structure which effectively combines military and law enforcement functions in the context of complex threats to national security.Based on the identified features, the individual areas of improvement of the National Guard of Ukraine as a law enforcement entity are formulated. Firstly, to integrate successful foreign experience into the domestic structure of the National Guard of Ukraine, since in many developed countries there are military formations that perform similar functions but have more experience and a different set of powers. Secondly, to continue developing the information space and transparency in it, as this is the way to build trust between the National Guard of Ukraine and the population. Thirdly, to pay special attention to the digitalisation of the National Guard of Ukraine as a law enforcement agency, which should also be linked to the improvement of the competence of the servicemen and women of the National Guard of Ukraine in building an inclusive security environment.
Keywords: National Guard; law enforcement; martial law; law enforcement agencies; law enforcement function.